Growth and foliar contents of N, P, K, Ca and Mg in peach cv. Diamante under different levels of N applied to the soil - Mattos, Maria Laura Turino; Freire, Cláudio José da Silva; Magnani, Marcio (Pesquisa Agropecuaria Brasileira, 1991)
An experiment with increasing levels of N was realized with the objective of determining the N content of the peach leaf related to better vegetative growth of the plants. The experiment had also the aim to evaluate N influence on foliar contents of P, K, Ca and Mg, using foliar analysis. The orchard consisted of 7 - years old peach trees of cultivar Diamante, spaced 4 m on the row and 6 m between the rows. The experimental design was completely randomized, with five replications. The treatments were 0, 135, 270, 405, 540 and 675 grams of N per plant, in the form of urea. Results obtained in 1985 through 1986 lead to the following conclusions: there was a linear positive correlation between plant vigor and N levels, in both vegetative cycles; there was also a positive quadratic correlation between N applied to the soil and N found in the leaves. Crescent levels of N decreased foliar contents of P, K, Ca e Mg.